2017
DOI: 10.11604/pamj.2017.26.161.10130
|View full text |Cite
|
Sign up to set email alerts
|

Le syndrome néphrotique idiopathique (SNI) de l’enfant à Dakar: à propos de 40 cas

Abstract: IntroductionL’objectif de ce travail était d’analyser les caractéristiques diagnostiques, thérapeutiques et évolutives de l’enfant atteint de néphrose dans un service de pédiatrie de Dakar.MéthodesL’étude était réalisée au service de pédiatrie de l’hôpital Aristide Le Dantec. Il s’agissait d’une étude rétrospective sur une période de 03 ans allant du 1er janvier 2012 au 31 décembre 2014. Ont été inclus tous les patients âgés de 02 ans à 12 ans présentant un tableau de Syndrome néphrotique idiopathique.Résultat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 14 publications
(20 reference statements)
3
11
1
Order By: Relevance
“…In our series, 50.00% of the children were in the 5-10 years of age. Our result was also comparable with 7.11 ± 3.14 years recorded in Senegal by Keita [9]. On the other hand, the mean age in Europe, Asia and America is approximately 5 years [8].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our series, 50.00% of the children were in the 5-10 years of age. Our result was also comparable with 7.11 ± 3.14 years recorded in Senegal by Keita [9]. On the other hand, the mean age in Europe, Asia and America is approximately 5 years [8].…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed that the male sex was mostly affected by this medical condition (61.64%) with a sex ratio of 1.60. This male predominance with a sex ratio of 1.85 was recorded by Keita Y, et al, in Senegal [9]. The majority of children came from regions located over 50 km away from Tanguiéta Health District.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In different parts of the world, several studies have been conducted on statural growth in children followed for INS with mixed results [11][12][13]. In Senegal, studies have been conducted on childhood INS without mentioning the impact of corticosteroids on their statural growth [14,15]. This evidence gap motivated our work, with the objectives to evaluate the frequency of statural growth retardation in nephrotic children on corticosteroids and to identify associated factors.…”
Section: Introductionmentioning
confidence: 99%